DAMPAK PERTUMBUHAN EKONOMI DAN UPAH RIIL TERHADAP PERMINTAAN TENAGA KERJA DKI JAKARTA 2005-2010 - Apriani Simatupang (Universitas Bunda Mulia, 2017)
This research studies the impact of economic growth and real wages through the demand of labor in DKI province from the 2005 to 2010. Problems of the research is formulated into two primary aspect. First, What is the impact of the DKI’s economic growth 2005 to 2010 through the demand of labor. Second, what is the impact of real wages through the demand of labor in DKI from 2005 to 2010. The secondary data from BPS Jakarta are use in this study with time series format from 2005-2010. The result are showing that economic growth and the real wage simultaneously affect to the demand of labor in DKI from period 2005 to 2010 which determinant cooficient is 0,83. It’s mean that the model which is proposed can explained 83% the variation of dependent variable. Economic growth have a positive impact meanwhile the real wages has the opposite impact to the demand of labor. Keywords- Economic growth, real wages, demand for labor